Spin-Polarized Positron Annihilation Measurement on Ga Vacancies in p-type GaN - Kawasuso, Atsuo; Sakai, Seiji; Miyashita, Atsumi; Maekawa, Masaki (E-journal of surface science and nanotechnology, 2018)
Nitrogen-implanted p-type GaN films have been investigated through the Doppler broadening of annihilation radiation (DBAR) measurements with spin-polarized positrons and magnetization (M—H) measurements. The DBAR spectra showed asymmetry upon magnetic-field reversal at 300 K, while no asymmetry appeared at 30 K. This result indicates that excess electron spins at Ga vacancies are aligned under the application of magnetic field at 300 K, but such spin ordering vanishes at low temperatures. No hysteresis was found in M—H curves both at 10 K and 300 K. This means that no macroscopic magnetism appears even though excess electron spins at Ga vacancies are introduced. [DOI: 10.1380/ejssnt.2018.347]